(3TQM GdMSjfI aj BOGH GdHMKs - (3GdOGQfOj, eMeO Hf YeQ Hf YKeGf, J (B1152 (3g`s ((3eMeO Hf SdjeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; EPG bdJe cdGeG fGbdG ajg Cj EPG UOQ efc cdGe hCfJ fGbd ajg eLQOI Yf GdJUMjM GdefGSH ddeWdH HCj hLg cGf ShGA cGf Gdefbhd eaQOG Ch eQcHGs
(3BNQgG (B:s
(3YfO GdefGXQI ShGA cGf ef GdSGFd Gh ef GdeYdd ajchf eDOjG dZdHI hgPG CTfY hLhg GdEdRGe hGdEaMGe hCTGQ GdeUfa Edi gPg GdKdKI Hbhdg abGd hCdaGX ZQjHI hdaX eLed hYO GdNUe VYja aJYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2 / 563s
(3EjVGM Gdecfhf (B1 /406s
(3gOjI GdYGQajf (B2 / 324s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs